Strategi Pemasaran Berbasis Online untuk Meningkatkan Penjualan Kue Soes di Kampus - Muhammad Sinar Randi; Andriani Marshanda Lubis; Ririn Marheni BR Barus; Sarina Wahyuni; Seri Rezjeki Wardani Tamba (Jurnal Kajian dan Penelitian Umum, 2025)
Soes cake has several advantages that make it attractive as a product to be marketed on campus. This study aims to analyze and design an online-based strategy. The research method used in this study is a mixture, which combines qualitative and quantitative approaches, namely practical soes can be consumed easily both while studying or relaxing, various flavors, affordable prices. Online-based marketing has become one of the most effective strategies in today's digital era. Online marketing strategies can help increase product accessibility, attract new customers and increase sales. This study aims to analyze and design an effective online-based marketing strategy to increase sales of soes cake on campus. The author routinely shares information about the latest products, special offers and even soca recipes to attract the attention of student group members as target consumers. Soes cakes generally have the characteristics of taste references.